Pengaruh Kepuasan Pasien Rawat Jalan Terhadap Waktu Tunggu Pelayanan Resep Obat Di Instalasi Farmasi RSUD Sawerigading Kota Palopo: The Effect of Outpatient Satisfaction on Waiting Time for Prescription Drug Services at the Pharmacy Installation of Sawerigading Hospital, Palopo City - Muslimin, Muhammad Ashar; Andi Sry Hardiyanti; Abd Razak (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2025)
The Hospital is a Health Service System That provides services for the community which includes Medical Services, Medical Support, and Nursing Services. Patient satisfication is the result of the patient’s assessment of the health services provided. The waiting time for prescription services at the hospital greatly influences patient satisfaction. This study aims to look at the effect of Patient Satisfication on Waiting Time for Prescription Services for Finished Medicines anda Compounded Medicines for outpatients at the Pharmacy Installation of Sawerigading Hospital Palopo City. The sample taken in this study was 230 people using Analytical Descriptive Research Design. From the result of the study obtained, the average waiting time for prescription services for finished medicines (9.2 minutes) and Compounded drugs (16,8 minutes) and has met standards set by the Hospital SPM according to the Indonesian Ministry of Health in 2018 and The Standard waiting time set by Sawerigading Hospital Palopo City. The result of the multivariate analysis obtained t = 10,128 and a Confidance Standard of 0.89. This Shows that waiting time affects the satisfication of outpatients in the Prescription Service of Sawerigading Hospital Palopo City.